Exploring self-leadership strategies and its proposed use among small and medium enterprise leaders in Nigeria - Nnaemeka, Enem Godwin; Mohd Anuar, Mohd Ashraff; Abdul Wahat, Nor Wahiza; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2020)
Self-leadership is a concept that aims to gain control on all aspect of life and individuals who practice self-leadership tend to improve on their performance. However, until recently the study of self-leadership has focused mainly on the personality of individuals, thereby neglecting the attitude of individuals and situational characteristics as crucial elements in self-leadership (Mutalib et al., 2013). This conceptual paper explores the self-leadership of small and medium enterprise (SME) leaders in Nigeria and investigates the crucial role the Nigeria business environment plays in the practice of self-leadership. The research methodology is qualitative descriptive research mainly relying on document analysis which constitutes an extensive review of relevant journals sourced from online platforms such as Google Scholars, Psycho.Net and from the researchers’ institutions online resources. The ideal leadership for SME leaders has been a contentious issue in recent times; therefore in this paper attention is also drawn on the SME knowledge and experience of their self-leadership. The findings show that situational factors such as technology, poor infrastructure and government policy affect self-leadership among SMES leaders. The practical implications suggest that self-leadership has the potential for individual leadership development and could be a strategy to enhance personal effectiveness and organizational development. Additional Self-leadership development opportunities are also required because the emerging realities which indicate the increasing demand for less supervision in organizations, and individuals are expected to be independent with higher performance.